PENGARUH DIGITAL MARKETING DAN STRATEGI PROMOSI DIGITAL TERHADAP PENINGKATAN PENJUALAN TENUN IKAT PADA WISNU MURTI GIANYAR BALI - Anggraeni, Dian (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: The aim of this study is to increase sales of ikat weaving at Wisnu Murti through digital marketing and digital promotion strategies, both of which are believed to be able to increase sales to the maximum. Keywords: Digital Marketing, Digital Promotion Strategies, Increase Sales